A study on customer's awareness of TOPS' private label of detergents at tops supermarket Shah Alam Mall / Nor Zurina Zulkifli - Zulkifli, Nor Zurina (1998)
This project paper is about A STUDY ON CUSTOMER'S AWARENESS OF TOPS' PRIVATE LABEL OF DETERGENTS AT TOPS SUPERMARKET SHAH ALAM MALL. The main issue that has been identified are customers not aware of TOPS' private label detergents and also promotions towards TOPS' private label detergents. The main objective of this study is to study on customer awareness of TOPS' private label detergents. Besides that this study also to know the successful of TOPS' private label detergents compare to others manufacturer's brand at TOPS Supermarket Shah Alam Mall. This study also to identify the type of customers that come to TOPS Supermarket and factors that influence them to purchase detergents and to give recommendations and suggestions for better promotion strategy to promote TOPS' private label detergents. The method used in this study are primary and secondary data collection. The primary data is through questionnaires while secondary data involved internal and external data collections.